Determinants of National Identity Among International Students Abroad - Utassy, Luca; Kozma, Dorottya Edina; Michalec, Gabriela; Ács, Sarolta (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
This study examines which factors shape national identity during study abroad, focusing on psychological, social, and institutional mechanisms. Using a cross-sectional survey design, data were collected from 308 international students studying in Hungary. Multiple linear regression analyses were conducted to examine how identity strain, intercultural engagement, host-country evaluations, and institutional satisfaction relate to post-mobility levels of national sentiment, patriotism, nationalism, and collective narcissism. The findings indicate that identity strain variables are the most consistent predictors of nationalism and collective narcissism. In contrast, greater international orientation and interaction with international peers are associated with lower levels of exclusionary national identity, while evaluations of the host country’s political, economic, and social conditions show inconsistent effects. The results suggest that national identity during study abroad is driven primarily by internal identity processes and relational exposure rather than host-country characteristics.